Model of Organic Fertilizer Self-Reliance Governance Based on Circular Economy in Supporting Food Security as a Pillar of Indonesia’s National Security - Firmansyah Firmansyah; Guntur Eko Saputro; Ummul Firmani (Yayasan Sembilan Pemuda Indonesia, 2026)
Food security has become a strategic issue closely linked to national security in many countries, including Indonesia. The dependence of the agricultural sector on imported chemical fertilizers exposes Indonesia to global supply chain disruptions, geopolitical tensions, and fluctuations in international commodity prices. This study aims to develop a governance model for organic fertilizer self-reliance based on the circular economy concept to strengthen food security as a pillar of national security. Using a qualitative approach through literature review and policy analysis, this article examines the relationship between circular economy principles, organic fertilizer production, food security, and national security. The findings indicate that organic fertilizer self-reliance contributes significantly to sustainable agricultural production, environmental resilience, economic independence, and social stability. The circular economy approach enables the conversion of agricultural, livestock, and household organic waste into valuable agricultural inputs, reducing dependence on external resources while enhancing soil fertility and ecosystem sustainability. Furthermore, effective governance involving government institutions, local communities, private sectors, and research organizations is essential for achieving sustainable fertilizer independence. The study proposes an integrated governance model that combines circular economy principles, food sovereignty, and national resilience. The model can serve as a policy framework for strengthening Indonesia’s food system resilience amid increasing global uncertainties.